1st Corinthians 13:4-8 - Tan, Zoe Yi Lin (Nanyang Technological University, 2020)
This project explores the adaptation of Bible narratives as an art form. Individual Bible stories are collectively selected with 1st Corinthians 13:4-8 as an umbrella topic - a set of verses from the Bible depicting fifteen characteristics of love. Bible stories are paired with each of these fifteen characteristics and wovened together to create a modern-day illustrated book of short stories.